In Memoriam: Wolfhart Pannenberg (1928–2014). (December 2014) - Peters, Ted
Abstract Prompted by the September 4, 2014 passing of a Continental titan of Protestant systematic theology, this article summarizes the life and thought of Wolfhart Pannenberg. A brief review is offered of his conversion from atheism to the Christian faith, student studies, and faculty positions along with his corpus of writings. An in‐depth analysis is offered of Pannenberg's key theological commitments to creation, eschatology, Christology, Trinity, retroactive ontology, prolepsis, anthropology, and the relationship between time and eternity. The scale and complexity and subtlety of Pannenberg's worldview renders it vulnerable to charges of incoherence; but few can doubt the masterful achievement of the gift of this person's life—a gift from God—to the world of Christian theology.